INCREASING THE POTENTIAL REGION ATTRACTIVENESS IN THE DEVELOPMENT ORDER INVESTATION - Winna Roswinna (Universitas Padjadjaran, 2020)
The purpose of this study is to examine the marketing of regional potentials that will improve the regional economy so that the Regional Government can reduce its dependence on financial assistance from the central government and gradually become a self-sufficient regional government. The methods use descriptive and explanatory survey with sample 200 respondents through simple random sampling, because homogeny respondents. The research result is creativity also involves marketing regional potential products and creating a comparative advantage for the region to attract investors. Creativity also concerns the ability of local governments to be able to attract Special Allocation Funds from the central government so that the central government does not hesitate to provide support in implementing development programs both social development programs and economic development programs as a product of marketing the potential of the region to be able to generate profits and benefits in order the implementation of regional autonomy for the welfare of the people in the region in a sustainable manner. The findings in this study are the physical infrastructure and human resources owned by the regions are elements that investors consider to invest.